2010
DOI: 10.1542/peds.2009-2717
|View full text |Cite
|
Sign up to set email alerts
|

Acute Confusional Migraine in an Adolescent: Response to Intravenous Valproate

Abstract: Acute confusional migraine (ACM) is a dramatic, rare manifestation of migraine described mostly for children and adolescents. There are few data on the treatment of an ACM attack. Prochlorperazine has been suggested as an effective drug. The authors of some reports have suggested that valproic acid may play a role in the prevention of ACM and as treatment for acute migraine headache in the adult population. However, this medication has not been reported as first-line, acute therapy for ACM. We report here the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Recent publications described “pediatric confusional migraine” cases in which valproate was efficacious. However, they did not investigate whether there was also photosensitivity [55, 56]. …”
Section: Role Of Photosensitivitymentioning
confidence: 99%
“…Recent publications described “pediatric confusional migraine” cases in which valproate was efficacious. However, they did not investigate whether there was also photosensitivity [55, 56]. …”
Section: Role Of Photosensitivitymentioning
confidence: 99%
“…Treatment : No specific therapy was mentioned in most case reports; however, some reports suggested efficacy of sodium valproate and prochloroperazine as treatment modalities for acute confusional state [ 12 , 19 , 21 , 22 ]. Prophylactic treatment with topiramate seems to be effective in the treatment of recurrent ACM [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…There have been few reports in the literature regarding the treatment of ACM. Avraham et al 12 reported a case of a young girl with a first episode of ACM that was responsive to valproic acid (VPA) during the acute confusional phase and intravenous VPA was suggested as an effective drug. In one of the preliminary studies carried out, Shahein et al 13 concluded that intravenous sodium valproate was found to be safe and rapidly effective for intractable migraine attack.…”
Section: Discussionmentioning
confidence: 99%